Development of a new standard procedure for the evaluation of composite abrasive wear - Bianchi, Eduardo Carlos [UNESP]; Silva, Eraldo Jannone Da [UNESP]; Monici, Rodrigo Daun [UNESP]; Xavier, Alexandre Pegoraro [UNESP]; Freitas, César Antunes De; Bianchi, Ana Rita Rodrigues (ABM, ABC, ABPol, 2001)
This article discusses the development of a test bench and a methodology for the study of composite resin abrasive wear. To evaluate the operation of the test bench and to compare the proposed methodology with other existing ones, a study was made of the five composites most commonly used by dentists. The one-way ANOVA method and the Tukey test were used to statistically analyze the results by multiple comparisons of the groups of resins tested. Using the proposed methodology, these resins were classified in an increasing order of abrasive wear strength, as follows: Charisma (the lowest abrasive wear strength), Tetric, TPH, Herculite and Z-100 (the highest abrasive wear strength) (p < 0.05). In comparison to other methodologies, the results of the proposed methodology presented the lowest coefficient of variation.
Keywords: abrasive wear; composites; composite tribology